The price of an egg: oocyte donor compensation in the US fertility industry. Issue 4 (2nd October 2017) - Johnson, Katherine M.
Abstract : Market-based health services have arisen out of major transformations in US healthcare in the last several decades. This study addresses pricing in the human egg donation market – an under-explored topic despite substantial scholarship on commodification and financial coercion of donors. Through analysis of primary data collected from 276 US fertility clinics and egg donation agencies, I assess what impacts average donor compensation and likelihood of compensation being more than $5000. Drawing on theories of organizational behavior, I test whether organizational characteristics, ecological factors, or regulatory pressure have the greatest impact on donor compensation amounts. I find that compensation is influenced primarily by ecological/market factors. Furthermore, industry self-regulation (measured by professional affiliation) did not deter clinics and agencies from having higher donor compensation levels, despite American Society for Reproduction Medicine recommendations. I conclude by addressing the broader implications of these findings for medical market dynamics and the problem of industry self-regulation.